Efficiency of local hyaluronic acid injections in subacromial impingement syndrome - V. A. Nesterenko; A. E. Karateev; E. I. Byalik; M. A. Makarov; S. A. Makarov; V. E. Byalik; M. R. Nurmukhametov; I. A. Fedotov (Научно-практическая ревматология, 2019)
Chronic shoulder pain associated with subacromial impingement syndrome (SIS) is a common pathology that causes suffering and disability. One of the treatments for SIS is the local injection of hyaluronic acid (HA) preparations.Objective: to evaluate the efficiency of subacromial injection of HA in chronic shoulder pain associated with SIS.Subjects and methods. A study group consisted of 31 patients (48.4% of women and 51.6% of men; mean age 53.8±15.2 years) with chronic shoulder pain (>3 months) that had occurred after rotator tendon injury confirmed by ultrasound and/or magnetic resonance imaging. All the patients received two subacromial injections of 40 mg HA in 2 ml at a 7-day interval. The efficacy criteria were the changes of pain during movement (100-mm visual analogue scale (VAS)) and functional ability according to the ASES and CSC questionnaires at 1, 3 and 6 months.Results and discussion. During the treatment, there was a considerable improvement in all measures. At baseline and 1, 3, and 6 months, the mean pain severity measured on VAS was 60.0±20.0, 40.0±25.4, 31.6±26.0, and 32.2±26.5 mm (p<0.001), the mean ASES scores were 53.64±16.43, 70.08±17.70, 86.13±12.86, and 82.69±27.88 (p<0.001); the mean CSC scores were 52.38±21.1, 66.26±20.83, 73.9±24.14, and 76.1±25.02 (p<0.001) respectively. No serious adverse events were noted.Conclusion. Subacromial injection of HA is an effective and safe treatment for chronic shoulder pain associated with SIS.